A critical review of the glaciomarine model for Irish Sea deglaciation; evidence from southern Britain, the Celtic shelf and adjacent continental slope - Scourse, James D.; Furze, Mark F.A. (My University, 2001)
In support of their ‘glaciomarine’ model for the deglaciation of the Irish Sea basin, Eyles and McCabe cited the occurrence of distal glaciomarine mud drapes onshore in the Isles of Scilly and North Devon, and of arctic beach-face gravels and sands around the shores of the Celtic Sea. Glacial and sea-level data from the southern part of the Irish Sea in the terminal zone of the ice stream and the adjacent continental slope are reviewed here to test this aspect of the model. The suggestion that the glacial sequences of both the Isles of Scilly and Fremington in North Devon are glaciomarine mud drapes is rejected. An actively calving tidewater margin only occurred early in the deglacial sequence close to the terminal zone in the south-central Celtic Sea. Relative sea-levels were lower, and therefore glacio-isostatic depression less, than envisaged in the glaciomarine model. Geochronological, sedimentological and biostratigraphical data indicate that the raised beach sequences around the shores of the Celtic Sea and English Channel were deposited at, or during regression soon after, interglacial eustatic highstands. Evidence for ice-rafting at a time of high relative sea-levels is restricted to a phase(s) earlier than the Late Devensian. These data indicate that the raised beach sequences have no bearing on the style of Irish Sea deglaciation.
Keywords: Irish Sea; continental shelf; glaciomarine; glaciomarine; raised beach; sea-level